Isocrates Free from Plato's Shadow - Ribas, Marie-Noëlle (Araucaria, 2020)
Isocrates is commonly remembered as a logographer or as a distinguishedprofessor of oratory, but never as a philosopher, although he persists in stylinghimself as such. No doubt this is largely due to Plato's criticism, which hassignificant influence on the way Isocrates is still considered. According to Plato,Isocrates who promotes a kind of philosophy with no regard to truth but only toopinion, does not deserve to be seen as an accomplished philosopher. Despitehis claims, Isocrates would fail to set himself apart from other sophists, withwhom he does not wish to be confused. In this article, I want to free Isocratesfrom Plato's disparaging view by showing what kind of philosophy Isocratesclaimed to teach.